The Effect of Board of Directors Narcism, The Board of Directors' Bonus Scheme, And The Ceo's Duality on Financial Reporting Quality - Suryadi, Suryadi; Fadjarenie, Agustin (Journal Research of Social Science, Economics, and Management, 2022)
This study aims to explain the effect of Board of Directors Narcissism on Financial Reporting Quality; the effect of the Board of Directors Bonus Scheme on the Quality of Financial Reporting; and The Effect of CEO Duality on Financial Reporting Quality. This research method is quantitative causal type which is asymmetric. The research locations are all state-owned companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The technique of collecting data is through surveys on secondary data on the IDX official website (www.idx.co.id). The data analysis technique is linear regression of panel data with the help of Eviews 9.0 software. The results showed that the Narcissism of the Board of Directors had a negative and significant effect on the Quality of Financial Reporting; The Board of Directors Bonus Scheme has a positive and insignificant effect on the Quality of Financial Reporting; and CEO Duality has a negative and insignificant effect on the Quality of Financial Reporting. The results of this study as input for the company are that the Narcissism of the Board of Directors, and Dualism of the CEO are not good for the company, so they must be prevented or minimized.